2021
DOI: 10.5304/jafscd.2021.102.051
|View full text |Cite
|
Sign up to set email alerts
|

A systems approach to navigating food security during COVID-19: Gaps, opportunities, and policy supports

Abstract: The COVID-19 pandemic has highlighted a series of concatenating problems in the global production and distribution of food. Trade barriers, seasonal labor shortages, food loss and waste, and food safety concerns combine to engender vulnerabili­ties in food systems. A variety of actors—from academics to policy-makers, community organizers, farmers, and homesteaders—are considering the undertaking of creating more resilient food sys­tems. Conventional approaches include fine-tuning existing value chains, consoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…COVID-19 cut these relationships and limited people's access to nutritious foods through lockdown restrictions [87]. Numerous evidence indicated that general consequences of the pandemic in the agricultural sector, including labor shortages, reduction of planting and harvesting, and reduction of agricultural trade, created an imbalance in the food system of many countries [88][89][90]. Although ecological constraints, such as climate change, water crisis, and land degradation, could significantly damage the prospects for economic growth and lead to food insecurity [91].…”
Section: Covid-19 Challenges Toward Sustainable Agriculturementioning
confidence: 99%
“…COVID-19 cut these relationships and limited people's access to nutritious foods through lockdown restrictions [87]. Numerous evidence indicated that general consequences of the pandemic in the agricultural sector, including labor shortages, reduction of planting and harvesting, and reduction of agricultural trade, created an imbalance in the food system of many countries [88][89][90]. Although ecological constraints, such as climate change, water crisis, and land degradation, could significantly damage the prospects for economic growth and lead to food insecurity [91].…”
Section: Covid-19 Challenges Toward Sustainable Agriculturementioning
confidence: 99%
“…Fardkhales and Lincoln (2021) describe the value of redundancy in diverse systems when responding to a crisis such as the COVID-19 pandemic. Glaros et al (2021) further explain how supply networks, as opposed to chains, work toward community resilience. This network perspective can be applied to the various sources of information utilized by businesses during immediate and prolonged crises.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to the specific characteristics of food systems in SIS, the governance regimes should have resilience and adaptive capacity. COVID-19 pandemic has even further highlighted the importance of policies that address greater levels of food resilience (Glaros et al 2021 ). The direction of decisional and institutional changes should be towards more flexible regulations and institutions that allow for context-specific implementations in different islands.…”
Section: Discussionmentioning
confidence: 99%